2002
DOI: 10.1002/zoo.10036
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different drying and storage methods on quantifiable concentrations of fecal steroids in the cheetah

Abstract: Fecal steroid analysis is a powerful tool that can provide important information on the health, physiology, and reproductive status of nondomestic species. However, studying free-ranging animals requires that feces be stored and transported from the collection site to the laboratory in a manner that prevents degradation or alteration of steroid metabolites. To determine the effects of different handling and storage methods on fecal steroids, 30 fresh fecal samples from five captive cheetahs were collected, tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 18 publications
4
74
0
1
Order By: Relevance
“…The origin of all these differences is the confluence of multiple causes pointed out by other authors: specificity of microbes in the feces that metabolize the fecal steroids, effect of temperature on steroid metabolite degradation, environmental moisture which allows the growth of microbes and fungi, change in metabolite affinity for antibodies, and the different chemical stability of each hormone (Matkovics 1972;Woods 1975;Neumann et al 2002;Terio et al 2002;Washburn and Millspaugh 2002;Millspaugh and Washburn 2004). Exhaustive condition-controlled laboratory metabolism studies, followed by precise identification of new metabolites, HPLC mass spectrometry, nuclear magnetic resonance, or infrared spectroscopy, are recommended to find out the precise hormone metabolism and degradation processes and the factors affecting them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of all these differences is the confluence of multiple causes pointed out by other authors: specificity of microbes in the feces that metabolize the fecal steroids, effect of temperature on steroid metabolite degradation, environmental moisture which allows the growth of microbes and fungi, change in metabolite affinity for antibodies, and the different chemical stability of each hormone (Matkovics 1972;Woods 1975;Neumann et al 2002;Terio et al 2002;Washburn and Millspaugh 2002;Millspaugh and Washburn 2004). Exhaustive condition-controlled laboratory metabolism studies, followed by precise identification of new metabolites, HPLC mass spectrometry, nuclear magnetic resonance, or infrared spectroscopy, are recommended to find out the precise hormone metabolism and degradation processes and the factors affecting them.…”
Section: Discussionmentioning
confidence: 99%
“…Because of microbial metabolism and other biochemical processes that occur over time, changes in humidity and temperature are probably the most influential environmental factors affecting steroid metabolite concentration in feces of free-ranging animals (Washburn and Millspaugh 2002;Terio et al 2002). Moreover, under field conditions, the fecal material undergoes changes in water content derived from its exposure to changing seasonal environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on the effects of medium-term storage on fecal steroids (e.g., Khan et al, 2002;Terio et al, 2002;Washburn and Millspaugh, 2002) have lagged behind those for urinary steroids (e.g., Brown et al, 1995;Grant and Beastall, 1983;Kesner et al, 1995), despite the recognition that, due to the bacterial load in fecal matter, steroids are inherently less stable in feces than in urine , and in fact, steroid levels can change within hours following defecation if samples are not immediately preserved (M€ o ostl et al, 1999). This study considers the effects of short-term, weeks-long, storage conditions on quantifiable fecal testosterone (fT), glucocorticoid (fGC), estrogen (fE), and progestagen (fP) concentrations in wild baboons (Papio cynocephalus).…”
Section: Endocrinologymentioning
confidence: 99%
“…Thus, the increase of the steroid concentration could be the result of the antibody cross-reactivity with other hormonal metabolites created by microbial transformation during storage (Terio et al, 2002). However, samples that were dried and stored in room temperature did not have significantly different fecal progestagen from initial concentration at 7 and 15 days.…”
Section: Effect Of Temperatures Of Short-term Storage On the Concentrmentioning
confidence: 99%
“…Other studies showed that ethanol has been used as a preservative for shortterm ambient temperature storage of fecal samples (Khan et al, 2002;Lynch et al, 2003). Furthermore, Terio et al (2002) suggested that storage of fecal samples at room temperature in ethanol was the best alternative to freezing for subsequent analysis of steroid hormone concentrations because it stabilized the concentrations of metabolites for progestogen and estrogen in cheetah for a period of up to 2 weeks. Other ambient temperature field storage techniques included drying samples.…”
Section: Introductionmentioning
confidence: 99%